Two pair‐rule responsive enhancers regulate wingless transcription in the Drosophila blastoderm embryo. Issue 4 (27th December 2019) - Bell, Kimberly; Skier, Kevin; Chen, Kevin H.; Gergen, John Peter
Abstract: Background: While many developmentally relevant enhancers act in a modular fashion, there is growing evidence for nonadditive interactions between distinct cis ‐regulatory enhancers. We investigated if nonautonomous enhancer interactions underlie transcription regulation of the Drosophila segment polarity gene, wingless . Results: We identified two wg enhancers active at the blastoderm stage: wg 3613u, located from −3.6 to −1.3 kb upstream of the wg transcription start site (TSS) and 3046d, located in intron two of the wg gene, from 3.0 to 4.6 kb downstream of the TSS. Genetic experiments confirm that Even Skipped (Eve), Fushi‐tarazu (Ftz), Runt, Odd‐paired (Opa), Odd‐skipped (Odd), and Paired (Prd) contribute to spatially regulated wg expression. Interestingly, there are enhancer specific differences in response to the gain or loss of function of pair‐rule gene activity. Although each element recapitulates aspects of wg expression, a composite reporter containing both enhancers more faithfully recapitulates wg regulation than would be predicted from the sum of their individual responses. Conclusion: These results suggest that the regulation of wg by pair‐rule genes involves nonadditive interactions between distinct cis ‐regulatory enhancers. Key Findings: Two distinct DNA elements within the Drosophila wingless locus that are associated with DNA‐binding proteins encoded by the pair‐rule segmentation genes mediate regulation by these genes in the early embryo. Neither of these two elements faithfully emulates the full range of wingless regulation in response to manipulations in pair‐rule gene activity. A composite reporter gene construct containing both enhancers more faithfully emulates wingless regulation than is expected from the sum of the expression patterns produced by the two single elements. The ectopic expression produced by the intronic enhancer is suppressed in a reporter gene construct that also contains the upstream enhancer element.